Implementation of Pancasila Values in Regional Head Leadership (Case Study: Hand of Love Assistance Program in the Leadership of Paulus Waterpauw 2020-2022 in West Papua Province) - Waterpauw, Paulus; Hanita, Margaretha; Runturambi, Arthur Josias Simon (Green Publisher Indonesia, 2024)
The